Hemolytic uremic syndrome as the presenting manifestation of WT1 mutation and Denys-Drash syndrome: a case report - Joseph L. Alge; Scott E. Wenderfer; John Hicks; Mir Reza Bekheirnia; Deborah A. Schady; Jamey S. Kain; Michael C. Braun (BMC Nephrology, 2017)
Abstract Background Hemolytic uremic syndrome (HUS) can occur as a primary process due to mutations in complement genes or secondary to another underlying disease. HUS sometimes occurs in the setting of glomerular diseases, and it has been described in association with Denys-Drash syndrome (DDS), which is characterized by the triad of abnormal genitourinary development; a pathognomonic glomerulopathy, diffuse mesangial sclerosis; and the development of Wilms tumor. Case presentation We report the case of a 46, XX female infant who presented with HUS and biopsy-proven thrombotic microangiopathy. Next generation sequencing of genes with known mutations causative of atypical HUS found that she was homozygous for the Complement Factor H H3 haplotype and heterozygous for a variant of unknown significance in the DGKE gene. Whole exome sequencing identified a de novo heterozygous WT1 c.1384C > T; p.R394W mutation, which is classically associated with Denys-Drash syndrome (DDS). At the time of bilateral nephrectomy five months after her initial biopsy, she had diffuse mesangial sclerosis, typical of Denys-Drash syndrome, without evidence of thrombotic microangiopathy. Conclusion This unique case highlights HUS as a rare but important manifestation of WT1 mutation and provides new insight into the genetics underlying this association.